GENDER EQUALITY IN R.A. KARTINI (2017) MOVIE: LAURA MULVEY’S PERSEPECTIVE - Hamdany, Muhammad Dziky (Universitas Negeri Surabaya, 2026)
This study analyzes gender equality in R.A Kartini (2017) movie. Laura Mulvey’s feminist perspective was used to frame the analysis, examining key themes such as patriarchal control, arranged marriage, women’s empowerment, and the representation of education. The study highlights how the film presents Kartini’s resistance to societal expectations and her determination to uplift women through knowledge and self-reliance. Using feminist theories, this research explores the broader implications of Kartini’s struggle in colonial Indonesia. The findings emphasize the film’s role in promoting feminist ideals and inspiring discussions on gender equality in contemporary society. Reflecting back to its goal, this study aims to interpret the message conveyed in a film by analyzing the content of the qualitative content analysis in the presentation of the story of the film Kehidupan Bunda Kartini (1982) which is a gender equality genre that depicts the struggle of R.A. Kartini in fighting for the rights of Indonesian women who at that time were still not equal to the rights of men in terms of getting education and so on (women's emancipation).